Answer:
g(3a – 6) = a - 4
Step-by-step explanation:
g(x) = 1/3x - 2
g(3a – 6) = 1/3(3a – 6) - 2
= a - 2 - 2
= a - 4
4x5-(2 (2) - 2 ) = 14
(18/ 3) + (3 (2) - 7) 8
Hey there!
b^2 - 5b + 3
= -3^2 - 5(-3) + 3
= -9 - (-15) + 3
= -9 + 15 + 3
= 6 + 3
= 9
Answer: 9
Good luck on your assignment and enjoy your day!
~Amphitrite1040:)
Answer:
A
Step-by-step explanation:
This is the answer because the others don't make sense to me at all...
<em>PLEASE</em><em> </em><em>DO</em><em> </em><em>MARK ME</em><em> </em><em>AS BRAINLIEST</em><em> </em><em>UWU</em><em> </em>
Please see the attached image for a visual representation of our scale factor. We can set up this proportion by taking the DVD cover and poster values and placing them in fractions. Cross multiply and divide to solve for x.